Future U.S. peacetime policy toward Russia exploring the benefits and costs of a less-hardline approach - Priebe, Miranda; Frederick, Bryan; Evans, Alexandra T.; Charap, Samuel 1980-; Tarini, Gabrielle; Rooney, Bryan (RAND, 2023)
"Whenever and however Russia's invasion of Ukraine ultimately ends, the U.S.-Russia relationship is likely to remain hostile in its aftermath. Over the long term, however, the United States will have incentives to reduce the risks and costs of its relationship with Russia in order to focus on other challenges, such as China. Future U.S. policymakers might therefore wish to again consider a limited less-hardline approach toward Russia. Supporters of such approaches contend that limited less-hardline approaches can reduce an adversary's insecurity, moderate its behavior, and reduce the costs and risks associated with competition between the two countries. Critics are reluctant to make concessions to U.S. rivals and worry that softening the U.S. stance could embolden a rival to become more demanding and aggressive. The authors used four historical case studies of limited less-hardline approaches with strategic similarities to the U.S.-Russia relationship before the war in Ukraine to evaluate these competing claims. These cases were (1) negotiations between Britain and Russia over Central Asia from 1899 to 1914 (2) U.S.-Soviet negotiations on the post-World War II order from 1945 to 1946, (3) the U.S.-Soviet détente from 1969 to 1975, and (4) the U.S.-Russia reset from 2009-2013. The authors found that such approaches have led to durable but narrow gains without emboldening the rival to be more demanding or aggressive. These limited policies also have limited effects. They only reduce a rival's threat perceptions modestly and do not prevent future deterioration of the relationship over outstanding conflicts of interest."
"RAND National Security Research Division"
Keywords: Geschichte 1899-2013; Außenpolitik; Militärpolitik; Außenbeziehungen; Geopolitik; USA; Russland; United States / Foreign relations / Russia (Federation)